Complications common in motorized intramedullary bone transport for non-infected segmental defects: a retrospective review of 15 patients - Mikužis, Mindaugas; Rahbek, Ole; Christensen, Knud; Kold, Søren (Acta Orthopaedica, 2021)
Background and purpose — Since the introduction of intramedullary bone transport nails only very few cases have been reported in the literature. Thus we evaluated the results and complications in a single institution retrospective cohort. Patients and methods — 15 (median age 40 years (18- 70), 8 males) consecutive patients, were included and the electronic patient records and radiographs were reviewed. Complications were severity graded and categorized as device or non-device related. Results — The segmental bone loss was due to non-union site in 8 femurs and 4 tibias, or traumatic bone loss in 2 femurs and 1 tibia. The segmental bone defect was a median of 3 cm (0.5–10). 9 of 10 femoral cases and 4 of 5 tibial cases healed with the bone transport nail. All 15 patients had a healed docking site and regenerate at the end of treatment after a median of 13 months (6–38). 24 complications (15 device related and 9 non-device related) occurred in 11/15 patients with a minimum follow-up of 6 months after nail removal. The number of unplanned surgeries due to device related complications was: 0 in 9 patients, 1 in 3 patients, 2 in 1 patient, 3 in 2 patients. Interpretation — Segmental bone defects can heal with a bone transport nail. However, the number of complications was high and 15 out of 24 complications were devicerelated. Optimizing nail design is therefore needed to reduce complications in intramedullary bone transport.